Text and Language Style in Early 20th Century Nusantara Ulama Manuscripts: Muhammad Amin Hasan Al-Banjari - Utami, Fajar; Indah Permata Sari; Fany Eka Amestia; Achmad; Erlina; Tamer Sa’ad Ibrahim Khodr (Universitas Islam Negeri Raden Intan Lampung, 2025)
The limited research on the socio-political influences on text structure and language style in the manuscripts of Nusantara scholars. This study analyzed the manuscript of Muhammad Amin Hasan al-Banjari to reveal reflections of the socio-political context and the intellectual expressions of scholars through language. Additionally, interpreting its linguistic features within the classical Islamic intellectual tradition presents complexities. This study aimed to examine the text and language style of the manuscript, focusing on its socio-political context and intellectual significance. The qualitative approach with textual analysis was used in this research. This study employed the manuscript of Muhammad Amin Hasan al-Banjari as its primary data source. The analysis involved identifying and interpreting thematic content, rhetorical techniques, and linguistic patterns found in the manuscript to understand the relationship between language structure and the socio-political context during the time of its writing. The findings revealed that the manuscript reflects the hardships of the Japanese occupation, using emotional descriptions, hyperbole, and repetition to emphasize suffering, while also conveying optimism about independence. It highlights the role of education in nation-building and the revival of Islamic scholarship as a response to colonial educational decline. The study contributes to understanding how ulama in Indonesia employed language to express intellectual resistance and national awakening. These findings provided insights into the intellectual history of the early 20th century and the role of manuscripts in shaping social and moral consciousness.